1993
DOI: 10.1128/jcm.31.7.1715-1725.1993
|View full text |Cite
|
Sign up to set email alerts
|

Major outbreak of pertussis in northern Alberta, Canada: analysis of discrepant direct fluorescent-antibody and culture results by using polymerase chain reaction methodology

Abstract: A major outbreak of 5,683 cases of pertussis occurred in northern Alberta, Canada, from December 1989 to January 1991. The outbreak highlighted a number of problems with current methods of pertussis diagnosis.In particular, an exceptionally high proportion of direct fluorescent-antibody (DFA)-positive, culture-negative specimens (88.4%) was identified. We took this opportunity to use polymerase chain reaction (PCR) methodology to examine whether the low culture rates were due to specimens containing dead organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(22 citation statements)
references
References 36 publications
1
20
0
1
Order By: Relevance
“…While in general this is true of our study as well, in our investigation the PCR assay was compromised by amplifying fixed material eluted from slides rather than sampling the clinical specimen directly. Indeed, a previous study demonstrated that the sensitivity of PCR drops 10-fold when it is performed with material eluted from slides rather than directly on suspensions of B. pertussis bacteria (9). In our study, there may have been an additional negative bias since the slides used for the PCR procedure were examined initially by the DFA test.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…While in general this is true of our study as well, in our investigation the PCR assay was compromised by amplifying fixed material eluted from slides rather than sampling the clinical specimen directly. Indeed, a previous study demonstrated that the sensitivity of PCR drops 10-fold when it is performed with material eluted from slides rather than directly on suspensions of B. pertussis bacteria (9). In our study, there may have been an additional negative bias since the slides used for the PCR procedure were examined initially by the DFA test.…”
Section: Discussionmentioning
confidence: 87%
“…Following DFA analysis, a subset of 100 slides, including those with discordant findings relative to culture, were analyzed for the presence of B. pertussis DNA by PCR. The DNA was recovered from bacteria and cell debris smeared on the slides essentially as described previously (9), by resuspending the material in 50 l of 12 mM Tris-HCl (pH 7.6) and then transferring the suspension to a microcentrifuge tube. Proteinase K (Sigma Chemical Co., St. Louis, Mo.)…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations